2000
DOI: 10.2114/jpa.19.135
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Mental Loads on Muscle Tension, Blood Pressure and Blink Rate.

Abstract: Surface electromyogram (EMG), blood pressure (BP), blink rate (BR) and heart rate (HR) were recorded before and during 4 types of mental task. The mental task involved 3 tasks that encompassed the memory (M), visual search (VS) and color-word (CW) tasks besides the control task (CT) of maintaining a similar posture while focusing on a single spot on the computer screen. Except for CW, any voluntary movement for response to visual stimuli given were not demanded. Slightly but significant increases in integrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 17 publications
4
34
0
Order By: Relevance
“…The increased surface EMG of the distal wrist extensor muscles observed in the present study is in line with data reported for a shoulder muscle, the trapezius muscle, under mental loads (Iwanaga et al, 2000;Laursen et al, 2002;Lorist et al, 2002;Lundberg et al, 1994;Nilsen et al, 2007;Schleifer et al, 2008;Visser et al, 2004). Specially, increased surface EMG activity was also reported in trapezius muscle when performing MA task (Lundberg et al, 1994).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The increased surface EMG of the distal wrist extensor muscles observed in the present study is in line with data reported for a shoulder muscle, the trapezius muscle, under mental loads (Iwanaga et al, 2000;Laursen et al, 2002;Lorist et al, 2002;Lundberg et al, 1994;Nilsen et al, 2007;Schleifer et al, 2008;Visser et al, 2004). Specially, increased surface EMG activity was also reported in trapezius muscle when performing MA task (Lundberg et al, 1994).…”
Section: Discussionsupporting
confidence: 92%
“…In the upper limb, studies have used surface EMG to evaluate the cognitive influences on motor system and reported global increases in surface EMG activity (Iwanaga, Saito, Shimomura, Harada, & Katsuura, 2000;Laursen, Jensen, Garde, & Jorgensen, 2002;Lorist, Kernell, Meijman, & Zijdewind, 2002;Lundberg et al, 1994;Nilsen, Sand, Stovner, Leistad, & Westgaard, 2007;Schleifer et al, 2008;Visser, de Looze, de Graaff, & van Dieën, 2004). Little is known about the behavior of single motor units (SMUs) when a cognitive task is performed.…”
Section: Introductionmentioning
confidence: 99%
“…By adding a decision making process to a simple lifting task, Davis et al (2002) found an increase in lumbar spine forces when the task was more complex. To increase mental or cognitive load, the Stroop test has often been used (Iwanaga et al, 2000;Lundberg et al, 2002;Fairclough and Houston, 2004) and it has been shown to cause activation in the anterior cingulated cortex (Gruber et al, 2002;Peterson et al, 1999). The Stroop test presents colour words appearing in an incongruent colour and requires the participant to verbally state the colour of the word rather than the word itself (Stroop, 1935).…”
Section: Introductionmentioning
confidence: 99%
“…Wu, Begley, Zhang, Adebisi, and Simpson (2011) [26] confirmed these findings and reported that eye blink rates decreased with greater concentration. When investigating changes in the eye blink rates of children engaged in video games, researchers have demonstrated a decrease in blinking when the game was in progress [27]. Kim, Min, and Park (2013) also confirmed these findings.…”
Section: The External Expression Of Flow Experiencementioning
confidence: 88%